Experimental Analysis of the Failure of the Bearing Support of a Cardan Shaft - Alvarado Silva, Carlos Alexis; De Souza, André Cristiano [UNESP]; de Oliveira, Geraldo Cesar Rosario [UNESP]; de Azevedo Silva, Fernando [UNESP]; Rubio, Bertha Ulloa (My University, 2022)
The work comprises the analysis of torque transmission line through cardans and the evaluation of how much the result from this methodology corresponds to failure of the cardan bearing support in a real application. Three different analyzes were carried out, first the entire methodology was understood and the analytical calculations of accelerations and loads of bearings were carried out, secondly, structural calculations were carried out via the Finite Element Method (MEF) with various types of loads, including those obtained through the analytical calculations and values of maximum and minimum normal stresses were generated as a function of each load.The stress results via MEF were compared with the stresses resulting from the third line of work obtained through the instrumentation of a gimbal bearing support in the field during the real application of the truck under analysis.A parametric spreadsheet was developed in order to carry out the analysis based on the theory / methodology, supporting the designer, reducing the approval time with the supplier, but it is necessary to continue research lines in this matter in order to predict with greater precision the dynamic behavior of the application of torque transmission lines through cardans.
Análise Experimental da Falha do Suporte de Mancal de um Eixo Cardan
Keywords: Cardan; Experimental Method; Extensometer; Fatigue; Finite Elements